Catalytic aerobic oxidation of 5-hydroxymethylfurfural into 2, 5-diformylfuran over VO2+ and Cu2+ immobilized on amino-functionalized core–shell magnetic Fe3O4@SiO2. Issue 97 (4th October 2016) - Liao, Longfei; Liu, Ying; Li, Zengyong; Zhuang, Junping; Zhou, Yanbin; Chen, Size
Abstract : Amino modified Fe3 O4 @SiO2 (Fe3 O4 @SiO2 –NH2 ) was used to immobilize Cu 2+ and VO 2+ for preparing Fe3 O4 @SiO2 –NH2 –Cu 2+ and Fe3 O4 @SiO2 –NH2 –VO 2+ catalysts. Abstract : Amino modified Fe3 O4 @SiO2 (Fe3 O4 @SiO2 –NH2 ) was used to immobilize Cu 2+ and VO 2+ for preparing Fe3 O4 @SiO2 –NH2 –Cu 2+ and Fe3 O4 @SiO2 –NH2 –VO 2+ catalysts. Various technologies had been used for the characteristics of catalysts, such as XRD, XPS, FT-IR, SEM, TEM and VSM. The catalytic performance of Fe3 O4 @SiO2 –NH2 –VO 2+ in HMF oxidation could be significantly enhanced by the use of Fe3 O4 @SiO2 –NH2 –Cu 2+ as the co-catalysts. The type of reaction solvents showed a great influence on the oxidation of HMF. The highest HMF conversion reached up to 98.7% at 110 °C in toluene with an optimal 2, 5-diformylfuran yield of 85.5%. Moreover, the Fe3 O4 @SiO2 –NH2 –Cu 2+ and Fe3 O4 @SiO2 –NH2 –VO 2+ catalyst exhibited great stability and could be readily applied in the next recycle after magnetic separation.